Poison A Play in one Act - Mdlongwa, Sandile (UJ Press, 2023)
The Gender Parity and Equality Committee is a team of five delegates from varying constituencies appointed by a legislative body that enacts, ratifies and repeals bills known as the People's Assembly. Their mandate is to produce a report on the state of gender politics, to be debated during a sitting of the Assembly to pass the Gender-Parity and Women Empowerment Bill. The sensitive nature of the topics around masculinity, femininity, sexual orientation, sexuality, gender and religion sees tensions brewing as early as the first committee meeting. Can middle ground be found where there are clashes in perceptions, moral compasses and perhaps a general lack of consciousness?